Differential responses to maternal diabetes in embryo and visceral yolk sac - Salbaum, J. Michael; Stone, Kirsten P.; Kruger, Claudia; Kappen, Claudia (Frontiers in Cell and Developmental Biology, 2023)
Maternal diabetes during pregnancy is well known to be associated with a higher risk for structural birth defects in the offspring. Recent searches for underlying mechanisms have largely focused on aberrant processes in the embryo itself, although prior research in rodent models implicated dysfunction also of the visceral yolk sac. There is a notable paucity of studies that investigate both tissues within the conceptus simultaneously. We therefore conducted unbiased transcriptome profiling by RNA sequencing on pairs of individual yolk sacs and their cognate embryos, using the non-obese diabetic (NOD) mouse model. The analysis was performed at gestational day 8.5 on morphologically normal specimen to circumvent confounding by defective development. Even with large sample numbers (n=33 in each group), we observed considerable variability of gene expression within each experimental group, which was primarily driven by exposure to maternal diabetes, and secondarily by developmental stage of the embryo. The exposure to diabetes distinctly influenced the relationship of gene expression levels to developmental progression, revealing a possible role for altered cell cycle regulation in the response to the exposure. We also identified cholesterol biosynthesis and NAD metabolism as pathways that have not been previously implicated in diabetic pregnancy.